A vaccine against atherosclerosis: myth or reality?. (March 2008) - van Puijvelde, Gijs HM; van Es, Thomas; Habets, Kim LL; Hauer, Arnaud D; van Berkel, Theo JC; Kuiper, Johan
Atherosclerosis is a chronic inflammatory disease that develops in the context of enhanced serum lipid levels. Nowadays, many studies focus on the modulation of inflammatory responses to reduce atherosclerosis. The most powerful strategy to achieve this is vaccination. In several immune diseases vaccination is shown to be very effective, resulting in a drastic decline in the incidence of the disease. But is vaccination also realistic in atherosclerosis? In this article, several approaches to vaccinate against atherosclerosis are described. Vaccination (based on protein or DNA) against bioactive molecules and disease-related proteins successfully reduces experimental atherosclerosis. In addition, passive immunization with antibodies against atherosclerosis-specific antigens and tolerance induction, in which antigen-specific regulatory T cells are elicited, are described. In the near future, we expect an increased interest in vaccination against atherosclerosis and, maybe, the myth may become reality when the first clinical trials are performed.